2011
DOI: 10.1002/hup.1226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol on highway driving in the STISIM driving simulator

Abstract: The STISIM highway driving simulator test is able to differentiate dose-dependent impairment after administration of alcohol. The highway driving test scenario is suitable for future psychopharmacological research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
65
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 22 publications
14
65
3
2
Order By: Relevance
“…Nor is there any significant interaction between BAC and simulator sickness for SDLP. This strengthens the notion that SDLP is a robust parameter of drug related driving impairment in simulator studies (Mets et al, 2011;Helland et al, 2013;Helland et al, 2016). Our results are in accordance with the findings in another simulator study (Muttray et al, 2013), where simulator sickness was found not to influence lane keeping behavior; however, the participants of that study reported very low simulator sickness scores.…”
Section: Discussionsupporting
confidence: 92%
“…Nor is there any significant interaction between BAC and simulator sickness for SDLP. This strengthens the notion that SDLP is a robust parameter of drug related driving impairment in simulator studies (Mets et al, 2011;Helland et al, 2013;Helland et al, 2016). Our results are in accordance with the findings in another simulator study (Muttray et al, 2013), where simulator sickness was found not to influence lane keeping behavior; however, the participants of that study reported very low simulator sickness scores.…”
Section: Discussionsupporting
confidence: 92%
“…6,7 The software and hardware simulation setup used has been previously validated in numerous studies. 18,20,22,25,35 Specifically, automobile components of the driving simulator included brake and accelerator pedals connected to a brake cylinder and force transducer, an adjustable steering column, and an adjustable car seat. The pedal assembly is connected to an analog-to-digital converter that transmits positional information to the computer.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, there is no well-defined, validated model with measurable end points that can truly evaluate upper extremity function in the context of driving performance. However, our position has been that through the use of a validated driving simulator, which has been used in a variety of studies both in the medical and in the orthopedic literature, 6,7,18,20,22,25,35 we have been able to create a customized driving circuit that directly tests upper extremity function in the context of driving by minimizing confounding variables such as variability in speed and braking, particularly in worst-case scenario situations that require coordinated evasive maneuvering.…”
Section: Collisionsmentioning
confidence: 99%
“…lateral control (SDLP) and longitudinal control (speed) (Lenné et al 2010;Mets et al 2011). Contrary to these results, the car following scenario with constant acceleration and deceleration of the lead vehicle previously failed to show alcohol effects (Veldstra et al 2011); it thus seems that it is notably in the period of stable speed by the lead vehicle that performance decrements occur.…”
Section: Discussionmentioning
confidence: 99%